Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/09669582.2016.1178754
|View full text |Cite
|
Sign up to set email alerts
|

The multiple logics of tourism development in China

Abstract: It has been widely demonstrated and accepted in the sustainable tourism literature that tourism development involves multiple stakeholders. However, little research has been conducted to examine the logics guiding and explaining the behaviours of the stakeholders in tourism development. Guided by the institutional logics perspective and stakeholder theory, this study identifies the logics of different stakeholders in China's tourism development through fieldwork in two tourism development cases (Yalong Bay and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…It also must be mentioned that many parts of China are experiencing rapid tourism development [65,66] and this is increasing the pressure on destination environments. Previous authors have acknowledged that government institutions are the main driving force spurring tourism development in China rather than the private sector or residents [65] and that socially and environmentally sustainable tourism development was not receiving enough attention [65].…”
Section: Research Limitations and Future Studiesmentioning
confidence: 99%
“…It also must be mentioned that many parts of China are experiencing rapid tourism development [65,66] and this is increasing the pressure on destination environments. Previous authors have acknowledged that government institutions are the main driving force spurring tourism development in China rather than the private sector or residents [65] and that socially and environmentally sustainable tourism development was not receiving enough attention [65].…”
Section: Research Limitations and Future Studiesmentioning
confidence: 99%
“…Third, previous research has found that coastal environments have considerable restorative potential (Hipp & Ogunseitan, 2011; White, Pahl, Ashbullby, Herbert, & Depledge, 2013). As such, Yalong Bay and Dadonghai, both recognized as mature and representative coastal resort destinations in China (Chen et al, 2016; Chen & Bao, 2014), offer a particularly appropriate setting in which to address the research questions.…”
Section: Methodsmentioning
confidence: 99%
“…According to China Tourism Academy (2019), 24.8% of Chinese urban residents travel for relaxation and taking a vacation. Second, Sanya is one of China's most successful and popular vacation cities (Chen, Huang, & Bao, 2016). In 2019, the total number of over-night tourist arrivals in the city of Sanya reached 23.93 million, in which the majority (96.22%) was domestic Chinese tourists (Sanya Statistical Bureau, 2020).…”
Section: Research Context and Study Areasmentioning
confidence: 99%
“…The tourism sector in Indonesia involves many actors (stakeholders) in its management (Bibin et al 2018, Chen et al 2016. The government, the community, and the private sector (companies) also participate in advancing tourism in Indonesia, including in Flory Village.…”
Section: The Role Of Stakeholdersmentioning
confidence: 99%
“…Further, Hwang et al (2012) emphasize CBT by preserving local identity and sustainability (Lee & Jan 2019). It needs multiple logic from various stakeholders with an institutional approach (Chen et al 2016).…”
Section: Introductionmentioning
confidence: 99%